Types of protest: essence and basic concepts (Journal of Philosophy Culture and Political Science, 2021)
Studying the types of protest, defining the essence and basic concepts is an urgent problem. The experience of protests demonstrates the presence of a number of unsolved socio-economic problems, insufficient effectiveness of the authorities in communication with society. The protest potential of society lies not only in the plane of socio-economic issues, but is formed on the basis of such factors: the level of political activity of citizens, relations between representatives of various ethnic groups, religions, ideologies, external information influence, etc. The role of the media is growing, both as tools for the dissemination of information and for the implementation of the political activity of citizens. New forms of protest are emerging, the study of which is important for understanding their direction, predicting possible options for the development of the situation and developing mechanisms to reduce negative consequences. This article reveals the essence and basic concepts of political, social and cultural protests. The main purpose of the article is to determine the characteristics of political, social and cultural protests by studying the reasons for their occurrence. The study conducted a literature review and a thematic analysis of data from scientific articles collected on the topic.Key words: protests, political protest, social protest, cultural protest.